PRIDE Annual Review 2007 - Kahl, Dan; Hoch, Connie; Stinson, Jeanne; Robl, J.R. (My University, 2007)
Summary of the 2007 actiivities of the Kansas PRIDE program and affiliated communities.
Keywords: Administrative and Research Reports; Community Development